PENINGKATAN EFEKTIVITAS ELEKTROKOAGULASI DAN FOTOKATALIS PADA PROSES DEGRADASI LIMBAH BATIK - angger sulistya; Tuhu Agung Rachmanto (EnviroUS, 2020)
Waste water from the batik industry process used the composition of naphthol generally contained organic pollutants that difficult to decomposed. This study discussed the efficiency treatment of batik industri waste water a combination of electrolyte and AOP approved methods in the electrocoagulation and photocatalyst process based on current density, electrolyte coordination and H2O2 composition. The parameters discussed include COD, TSS, color, TDS and pH. In a batch process conducted with 5 liters of water that fixed by current density (A/cm2) and NaCl electrolyte (gr/L) in electrocoagulation and 30% H2O2 concentration (mg/L) were determined as photocatalytic variables. In addition to batches, this study also carried out continuous experiments with the best variables from the batch process. Efficiency of the percentage reduction in COD, TSS, color, TDS and pH used electrocoagulation and photocatalyst were 87.8%, 84.01%, 94.07%, 32.9% and pH respectively 7,3 at a contact time of 120 minutes.